PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VIII MTs SYEKH LOKIYA TOWALE PADA MATERI LUAS PERMUKAAN KUBUS DAN BALOK: APPLICATION OF THE STAD TYPE COOPERATIVE LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS VIII MTs SYEKH LOKIYA TOWALE ON SURFACE AREAS OF CUBS AND BEAM MATERIALS - Riana, Nurul; Nurhayadi; Hasbi, Muh. (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
The main objective of this study was to obtain a description of the application of the student teams achievement divisions type cooperative learning model to improve student learning outcomes on the Surface Area of Cubes and Beams. This research is Classroom Action Research (PTK) which refers to the research design of Kemmis and Mc. Taggart, namely (1) planning; (2) implementation of actions and observations; and (3) reflection.. Application of the STAD type cooperative learning model that can improve the learning outcomes of class VIII MTs sheikh Lokiya Towale students on the Cube and Beam Surface Area material following the STAD type cooperative learning steps, namely: 1) Conveying learning objectives and motivating students;2) Presenting/delivering material; 3) Organizing students into cooperative groups; 4) Guiding work and study groups; 5) Evaluation; and 6) Awarding. The subjects of this study were class VIII MTs student Sheikh Lokiya Towale who totaled 14 students and three students were selected as informants. This research was carried out in two cycles. The results showed that in the final test of cycle I there were 6 students who were completed and 7 students who were not completed with the percentage of classical completion reaching 46.15% while in cycle II there were 9 students who were complete and 3 students who were not completed with the percentage of classical completion reaching 75%. The results of the observation of teacher and student activities in cycle II in participating in learning are in the very good category. Based on the results of the research obtained, it can be concluded that the application of the STAD type cooperative learning model to improve the learning outcomes of Class VIII MTs students Sheikh Lokiya Towale on the surface area material of cubes and blocks.